Towards Sustainable Consumption: Consumer Behavior and Market Segmentation in the Second-Hand Clothing Industry - Razvan-Andrei Corbos; Ovidiu-Iulian Bunea; Monica Triculescu (Amfiteatru Economic, 2023)
In this study, we use bibliometric analysis as a quantitative and systematic approach to assess the scientific landscape and present the existing literature, focusing on the consumer buying behaviour of second-hand clothing in the context of sustainability. We observe a decrease in the number of published papers on this topic, as evidenced by the limited number of papers in the Web of Science (WoS) database (41 papers) and Scopus (38 papers). Through co-occurrence analysis, we highlight the importance of consumer behaviour research in sustainable fashion and identify research gaps related to the absence of market segmentation analysis based on consumer behaviour and demographic information in the second-hand clothing market. To address these gaps, our research aims to identify the main factors that influence consumers to buy second-hand clothing products and to examine the profile of customers who make these purchases, focusing specifically on Romania. We collected data from 110 respondents through a questionnaire. Using two-stage clustering and ANOVA, we identify distinct consumer segments that share similar characteristics. These segments show variations in age, income, frequency of purchase, and reasons for choosing second-hand clothing. By addressing sustainability concerns and providing practical strategic options, our study aims to help businesses operating in the second-hand clothing market. Our findings align with previous research on diverse consumer segments with different attitudes and behaviours towards second-hand consumption.
Keywords: Q01; Q56; 330; consumer behavior; second-hand clothing; market segmentation; sustainability; strategic options